Investigation of the oxide phase convective homogenization while vacuum-arc with hollow cathode remelting of steel - Andreeva, Oksana; Borts, Boris; Kostikov, Andrii; Tkachenko, Victor (Eastern-European Journal of Enterprise Technologies, 2016)
Discussion of the requirements for the placement of ZrO2 powder in the cathode, which must be taken into account in the production of ODS steel by vacuum-arc remelting in order to provide the high level of homogenization of the oxide particle is presented. The description of the experimental setup and the cathode structure for vacuum-arc remelting of steel, alloyed with oxide nano-powder is given. The role of convective processes in the homogenization of nano-particles in the production of ODS steel is highlighted. The convective flow of liquid metal captures ZrO2 powder particles and carries them throughout its volume. The use of the elementary cylindrical convective cell with mixed boundary conditions is proposed for the description of homogenization of the oxide particles. The structure and spatial distribution of the convective mass transfer in the cylindrical convective cell with the cosinusoidal bottom profile are provided. Spatial distribution of convective flow in the cell is described by the Stokes lines, which are concentrically arranged smooth closed lines, which indicates the formation of convective flow in the form of a single vortex in the cell with mixed boundary conditions. Near the bottom, the Stokes lines reflect the curved cosine bottom profile. Criteria of vacuum-arc melting and convective mixing of ZrO2 nano-particles are formulated. Drops of the liquid material of the cathode with ZrO2 nano-particles penetrate to the central vertical flow of the convective cell. Then, near the wall of the crystallizer, the particles are subjected to vertical forces: Archimedes force (always directed in vertical direction, i.e. upwards); gravity force (always directed downwards); friction force (Stokes force) (directed along the liquid velocity vector) on these particles. The Archimedes force depends on the volume, i.e. size, of the particle. Thus, the less the nano-particle size, the lower the buoyancy force. The criterion of overcoming the Archimedes force allows determining the sizes of the particle at which their uniform distribution in the cell volume is possible. Criteria of convective homogenization ZrO2 nanoparticles are the following: – droplets of cathode material penetrate into the cylindrical convective cell on a circular line which corresponds to the inner circumference of the hollow cathode; – drops of the cathode material penetrate to a depth of convective cells, consistent with its half-height; – ZrO2 particles with sizes less than 90 nm will be stored for a long time in the melt, and homogenized in volume of the melt as a result of convective mass transport.